2010
DOI: 10.1111/j.1365-2966.2010.17619.x
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of 59 ms pulsations from 1RXS J141256.0+792204 (Calvera)

Abstract: We report on the results of a multi‐wavelength study of the compact object candidate 1RXS J141256.0+792204 (Calvera). Calvera was observed in the X‐rays with XMM–Newton/EPIC twice for a total exposure time of ∼50 ks. The source spectrum is thermal and well reproduced by a two‐component model composed of either two (absorbed) hydrogen atmosphere models or two blackbodies with temperatures kT1∼ 55/150 eV, kT2∼ 80/250 eV, respectively (as measured at infinity). Evidence was found for an absorption feature at ∼0.6… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
104
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(112 citation statements)
references
References 61 publications
8
104
0
Order By: Relevance
“…Frequency measurements from the two XMM-Newton observations of Calvera acquired by Zane et al (2011), as reduced by Halpern (2011), are also listed in Table 1 and shown in Figure 2. None of the observations are closely spaced enough to link coherently and obtain more precise timing parameters.…”
Section: Figurementioning
confidence: 99%
See 4 more Smart Citations
“…Frequency measurements from the two XMM-Newton observations of Calvera acquired by Zane et al (2011), as reduced by Halpern (2011), are also listed in Table 1 and shown in Figure 2. None of the observations are closely spaced enough to link coherently and obtain more precise timing parameters.…”
Section: Figurementioning
confidence: 99%
“…It was not until a pair of XMMNewton observations was obtained with high time resolution that Zane et al (2011) discovered the 59 ms pulsations from Calvera. The X-ray emission from Calvera is best described by a twotemperature (blackbody or hydrogen atmosphere) spectrum, with kT in the range 0.1-0.25 keV (Shevchuk et al 2009;Zane et al 2011). The fitted column density in these models is equal to or greater than the Galactic value of N H = 2.7 × 10 20 cm −2 (Kalberla et al 2005), which, at its high Galactic latitude of +37…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations